2016
DOI: 10.1177/1077546316648811
|View full text |Cite
|
Sign up to set email alerts
|

Active control of hybrid electric vehicle launch vibration in pure electric mode

Abstract: Sudden torque changes and torque fluctuations caused by a traction motor in HEV (hybrid electric vehicle) can result in a driveline oscillation. This paper focuses on the HEV launch vibration in pure electric mode while only the electric motor is generating output torque. A relevant mathematical model has been built based on the working principle. According to the model, the torsional vibration characteristics of the electric propulsion system have been analyzed. Two active control methods, feed-forward contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For the sake of designing the active controller, the moment of inertia of the planetary gear is overlooked. The dynamic relationship of the Ravigneaux planetary gear set can be replaced by equation (12).…”
Section: The Reducer and The Differentialmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of designing the active controller, the moment of inertia of the planetary gear is overlooked. The dynamic relationship of the Ravigneaux planetary gear set can be replaced by equation (12).…”
Section: The Reducer and The Differentialmentioning
confidence: 99%
“…To control this kind of torsional vibration, compared with feed-forward control and PP, WSCS has the best effect. 12 The concept of WSCS is to delay part of the input to superimpose with the original input to eliminate the output wave. The control strategy is as shown in Figure 9.…”
Section: Controller Designmentioning
confidence: 99%
“…Liu et al 4 suggested a method for regulating torsional vibration under parameter uncertainty conditions, integrating reference adaptive control and pole position, and the control realized the suppression of output shaft torque ripple under shock conditions. Also, other control methods like robust energy peak control, 5 feed-forward control, 6,7 PID algorithm, 8,9 linear quadratic regulator (LQR) control, 10 model predictive control (MPC), 11 and wave-electric superposition (WSCS) control 12 were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A wave superposition control strategy was applied to suppress the HEV launch vibration. 28 A two mass-spring damper linear model was proposed in Zhong and Wei 29 to develop a torsional vibration control algorithm based on state feedback. In Zhang et al., 30 an LQG controller with an estimator was implemented.…”
Section: Introductionmentioning
confidence: 99%